Kisah Dzulqarnain dalam Al-Qur'an - Hamdani Anwar (Refleksi: Jurnal Kajian Agama dan Filsafat, 1998)
This study presents one of the stories in the Qur'an, namely about the figure of Dhul-Qarnayn. This figure is interesting to discuss because his existence is often associated with various famous figures in human history. The mufassirun have diverse opinions regarding the true identity of Dhul-Qarnayn. Additionally, there is the notion that the story about him might merely be symbolic, meaning that this figure never definitively existed in history. This research aims to address these issues through thorough analysis and exploration of related verses, interpretations by scholars, and argumentative comments from intellectuals. The results of this study are expected to provide a deeper understanding of the story of Dhul-Qarnayn in the Qur'an.